Performance trends in age‐group runners from 100 m to marathon—The World Championships from 1975 to 2015. (30th January 2017) - Nikolaidis, P. T.; Zingg, M. A.; Knechtle, B.
Abstract : This study examined changes in performance in age‐group track runners across years from 1975 to 2015 for 100, 200, 400, 800, 1500, 5000, 10 000 m, and marathon and the corresponding sex differences. Athletes were ranked in 5‐year age‐group intervals from 35‐39 to 95‐99 years. For all races and all years, the eight female and male finalists for each age‐group were included. Men were faster than women and this observation was more pronounced in the shorter distances. The younger age‐groups were faster than the older age‐groups and age exerted the largest effect on speed in 800 m and the smallest in marathon. There was a small variation of speed by calendar years. The competition density varied by sex and race distance. Half of participants were from USA, Germany, Australia, and Great Britain, but the participants' nationality varied by sex and race distance. In summary, the variation of competitiveness by sex in short race distances might be important for athletes and coaches. Considering the event's competitiveness and that athletes are participating in both 100 and 200 m or in 200 and 400 m, master women should be oriented to 200 m and master men should be oriented to 100 and 400 m.